The Teachers’ Perceptions Towards The Use of The Textbook Developed by Erlangga for Eleventh Grade Students - Dewi, Zevikurniasari; Sukmaantara, I Putu; Wijaputra, Bambang Arya (English Education Study Program, 2021)
Textbooks have a vital role in the teaching and learning process, especially in a foreign language classroom. Unfortunately, not all the published textbook are appropriate to be used in the classroom. Therefore, this study focuses on teachers‟ perception towards the use of eleventh-grade textbook developed by Erlangga. The research design was descriptive qualitative. The research participants were teachers. Measured using Tentative Evaluation Checklist ByNimechisalem and Mukundan.The Participants were eleventh-grade teachers from MAN 1 and MAN 2 Jember. Based on the result from eleventh-grade teachers‟ perceptions showed that The English Textbook published by Erlangga have the most weakest aspect that need more development.